EFEKTIFITAS METODE TANYA JAWAB BERBASIS BAHASA JAWA UNTUK MENINGKATKAN KEMAMPUAN BAHASA ANAK KELOMPOK A DI TK DHARMA WANITA NOGOSARI: EFFECTIVENESS OF THE JAVANESE LANGUAGE-BASED QUESTION AND ANSWER METHOD TO IMPROVE THE LANGUAGE SKILLS OF GROUP A CHILDREN AT DHARMA WANITA NOGOSARI KINDERGARTEN - Khusnul Khotimah; Dwi Bhakti Indri M (Jurnal Intelek Insan Cendikia, 2024)
Abstract Language is the identity of a nation that is very important to apply from an early age. Because language can reflect a person's ethnicity, customs of origin. Language is very important to develop from an early age because language will affect the child's ability to speak and will affect the child's cognitive. In everyday life, the language given to children should be a language that can show the child's identity such as Javanese. Because with the development of this era, Javanese language began to be displaced by other foreign languages so that children forget their mother tongue. For this reason, the introduction of Javanese can be done with the Javanese-based question and answer method accompanied by loose part media in accordance with current curriculum developments. This study aims to determine the effectiveness of the Javanese language-based question and answer method using loose part media which aims to improve children's language skills, especially group A children at Dharma Wanita Nogosari Kindergarten. By using quantitative research methods of experimental research type by using one group pretest - post test design. This research was conducted by taking a sample of group A students with a total of 9 children with data collection techniques using observation, questionnaires and documentation. To determine the significant value, this study used the normality test with the help of IBM SPSS Statistics 29.0.2.0. The results of this study indicate the effectiveness and influence on improving children's language skills by using the Javanese language-based question and answer method using loose part media with the highest pretest score of 46 and the highest post test score of 69 with the results of the normality test 0.83> 0.05. So it can be concluded that there is an effectiveness of using the Javanese language-based question and answer method using loose part media in improving children's language in group A of Dharma Wanita Nogosari Kindergarte. Keywords: Question and answer method, Javanese